Hyperbaric Oxygen Therapy in the Treatment of Idiopathic Sudden Sensorineural Hearing Loss - Debashish Guha; Shaoni Sanyal; Chayan Bhattacharya; Abhijit Santra; Swagatam Banerjee (Bengal Journal of Otolaryngology and Head Neck Surgery, 2015)
Backgrounds and objectives Idiopathic sudden sensorineural hearing loss (ISSNHL) is an entity whose diagnosis and treatment remain controversial to date. Various modalities of treatment have been tried with varying degrees of success. Hyperbaric oxygen therapy (HBOT) is a recent modality of treatment for this condition which acts by improving cochlear microcirculation. The objective of this study was to evaluate the effect of HBOT in improving hearing loss and secondary symptoms patients with ISSNHL. Methods This prospective study was undertaken over a 6 month period from the Department of Otorhinolaryngology in a tertiary referral hospital in eastern India. 48 consecutive newly diagnosed ISSNHL patients were included in this study. The patients were subjected to HBOT at 2 A.T.A (Atmosphere Absolute) for an hour over 45 days. Hearing status and secondary symptoms as assessed by clinical tests, pure tone audiogram were analysed before and after HBOT. Results Males comprised 62.5% (30/48) of our study population, mean age of the population was 49.3 ± 13.4 years. 45/48 patients (93.7%) had unilateral ISSNHL, while 3 (6.3%) had bilateral ISSNHL. Average hearing loss in the affected ear before and after treatment was 79.96dBHL and 62.27dBHL respectively. The most common secondary clinical feature was tinnitus (27/48, 56.3%), followed by vertigo (24/48, 50%), aural fullness (15/48, 31.25%) and nystagmus (5/48, 10.41%). After treatment tinnitus and vertigo were showed marked improvement; (22/27, 81.48%) and (18/24, 75%). 5 out of 15 (33.34%) patients showed reduced aural fullness. There was no improvement in patients suffering from nystagmus.